2020
DOI: 10.1242/dev.188011
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal phosphorylation modulates ERM-1 localization and dynamics to control cortical actin organization and support lumen formation during Caenorhabditiselegans development

Abstract: ERM proteins are conserved regulators of cortical membrane specialization that function as membrane-actin linkers and molecular hubs. The activity of ERM proteins requires a conformational switch from an inactive cytoplasmic form into an active membrane- and actin-bound form, which is thought to be mediated by sequential PIP2 binding and phosphorylation of a conserved C-terminal threonine residue. Here, we use the single Caenorhabditiselegans ERM ortholog, ERM-1, to study the contribution of these regulatory e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 80 publications
(141 reference statements)
15
47
0
Order By: Relevance
“…10 We therefore generated an endogenous IFB-2::mCherry fusion and analyzed the localization of BBLN-1 relative to IFB-2 and ERM-1, which localizes to microvilli. 29,30 Consistent with localization to the endotube, we found that BBLN-1 co-localized with IFB-2, basal to ERM-1 (Figures 2C and 2D). To determine whether BBLN-1 stably associates with the IF network, we performed fluorescence recovery after photobleaching (FRAP) experiments.…”
Section: Loss Of Bbln-1 Causes Cytoplasmic Invaginations Of the Intestinal Apical Membranesupporting
confidence: 77%
“…10 We therefore generated an endogenous IFB-2::mCherry fusion and analyzed the localization of BBLN-1 relative to IFB-2 and ERM-1, which localizes to microvilli. 29,30 Consistent with localization to the endotube, we found that BBLN-1 co-localized with IFB-2, basal to ERM-1 (Figures 2C and 2D). To determine whether BBLN-1 stably associates with the IF network, we performed fluorescence recovery after photobleaching (FRAP) experiments.…”
Section: Loss Of Bbln-1 Causes Cytoplasmic Invaginations Of the Intestinal Apical Membranesupporting
confidence: 77%
“…To confirm that BBLN-1 resides at the endotube, we generated an endogenous mCherry fusion of the intestinal intermediate filament protein IFB-2. We then analyzed the localization of BBLN-1 relative to IFB-2 and to ERM-1, which localizes apically at microvilli (Bidaud-Meynard et al, 2019; Ramalho et al, 2020). Consistent with localization to the endotube, we found that BBLN-1 colocalizes with IFB-2, basal to ERM-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The central lumen is surrounded by a thick electron-dense terminal web [ 25 ] (also seen in the nematode and mammalian intestine, among many other tissues) composed of actin filaments and intermediate filaments. Actin is held to the apical membrane by the Ezrin-Radixin-Moesin homologue ERM-1 [ 26 ], which itself is activated via phosphorylation of a terminal domain upon binding to phosphatidyl inositol 4,5-bisphosphate (PIP 2 ) lipid on the apical (luminal) surface [ 27 ]. Overlapping and surrounding the actin cytoskeleton is a thick layer of three intermediate filament proteins, IFA-4, IFB-1, and EXC-2/IFC-2 [ 22 , 28 ].…”
Section: Anatomy Of the Canal Cellmentioning
confidence: 99%